Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2016
DOI: 10.1115/gt2016-56038
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Power Operation of a Supercritical Carbon Dioxide Brayton Cycle With Thermal-Hydraulic Control

Abstract: The Bechtel Marine Propulsion Corporation (BMPC) Integrated System Test (IST) is a two shaft recuperated closed Brayton cycle using supercritical carbon dioxide (sCO2) as the working fluid. The IST is a simple recuperated Brayton cycle with a variable speed turbine driven compressor and a constant speed turbine driven generator designed to output 100 kWe. The main focus of the IST is to demonstrate operational, control, and performance characteristics of an sCO2 Brayton power cycle over a wide range of conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Linares et al [13] proposed a modification to RCBC that facilitate heat addition at a lower pressure to enable the use of conventional shell and tube heat exchangers in order to reduce the cost of the PHEX for CSP applications. Clementoni et al provided the steady-state [14], off-design [15] and transient [16] operational results of a 100kWe experimental facility at the Naval Nuclear Laboratory, USA. Clementoni et al [17] also reported the operational results of the test facility for different compressor inlet temperature (CIT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linares et al [13] proposed a modification to RCBC that facilitate heat addition at a lower pressure to enable the use of conventional shell and tube heat exchangers in order to reduce the cost of the PHEX for CSP applications. Clementoni et al provided the steady-state [14], off-design [15] and transient [16] operational results of a 100kWe experimental facility at the Naval Nuclear Laboratory, USA. Clementoni et al [17] also reported the operational results of the test facility for different compressor inlet temperature (CIT).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have performed transient simulations of the standard recompression cycle [10][11][12][13][14], finding that inventory control provides higher efficiency at part load compared to other control techniques such as turbine bypass, turbine inlet temperature and throttling control. Inventory control turndown is limited, however, by the size of the CO2 storage tank and the pressure pinch between that storage tank pressure and the system pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, owing to these advantages of sCO 2 power generation, numerous studies are underway, primarily in developed countries. Sandia National Lab (SNL) proposed and tested a 250 kW sCO 2 Brayton cycle [1,2]; Bechtel Marine Propulsion Corporation (BMPC) also proposed a 100-kW CO 2 Brayton cycle integrated system [3,4]. Echogen developed a 7.3-MW sCO 2 power cycle for waste heat recovery system [5].…”
Section: Introductionmentioning
confidence: 99%